PENYELESAIAN SENGKETA TANAH HAK GUNA USAHA PT. EMHA DENGAN KELOMPOK TANI SEKAR RUKUN DI KECAMATAN SEI SUKA KABUPATEN BATUBARA - Nainggolan, Netty Herawati (JURNAL MERCATORIA, 2016)
The goal is for people to live a decent to cultivate land for farming. Status of land given is working on with the results. From the evidence of authentic evidence obtained in this study indicate lack of clarity and inaccuracies of data data about the status of the land and the agreement made, then there is the impression created by the origin of data. Weakness conducted by farmer groups Sekar Pillars is a land dispute was later abandoned due to land into a swamp, while the agreement was made clear when abandoned land will be taken over by the government. Other facts obtained in the field that the land will be taken over by the government were not followed up after a while the land is abandoned, with the reasons and circumstances to bring this dispute to PT. Emha as holder of leasehold land bordering the dispute. Clarity of the government in this case the Minister of Agrarian / Head of National Land Agency have nothing to say that the land has been given to PT. Emha, this is what triggers the problem after PT. Emha enter eskapator to process and flatten the land dispute.